(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The paper considers the critical nature of surrogacy, assessing risks connected to the practice in the absence of an international regulation and identifying fundamental rights in need of protection. It also evaluates the compatibility of surrogacy with existing international law instruments and analyses the relevant case-law of the European Court of Human Rights. Despite the compatibility of surrogacy with some treaty provisions is strongly controversial, the Author argues the need for an international instrument on the practice.